Results of histological examination of experimental diabetic retinopathy and its correction with metformin, aflibercept, L-arginine solution and cyticolin - Sirman, Y.; Savytskyi, I.; Preys, N.; Blavatska, O. (Journal of Education, Health and Sport, 2020)
The purpose of the study was to analyze the histological changes in the structures of the eyeball in experimental diabetic retinopathy and its correction with metformin, aflibercept, L-arginine solution and citicoline. The obtained results indicate about the development of pathological changes in the retina against the background of the progression of experimental diabetes when streptozotocin is administered at dose 55 mg/kg of animal weight against the background of a high-fat diet. The development of simulated streptozotocin diabetes is accompanied by disturbance in the retina in the form of edematous shifts of fibers and swelling of the cells forming it, uneven distribution of cells of the ganglion layer and vacuolization of the cytoplasm some of them. The using of corrective drugs complex for metabolic disorders and angiopathy, which are characteristic of diabetes mellitus, affects on the retina condition. Under the influence of aflibercept, solution of L-arginine, citicoline, and metformin administration was established that edematous changes in its structural elements are significantly reduced, the number of vessels on the border with the retina visually increases, and the staining of the cells of the ganglion layer becomes more freshly.